Unsichtbare Schatten : Bilder der Verunsicherung - Niemeyer, Thomas; MARTa Herford (Herford, Germany) ([Herford] : MARTa Herford, 2010)
Ardeleanu, Mona ; Bitzer, Matthias ; Borremans, Michaël ; Bradford, Mark ; Burwitz, Baldur ; Canell, Nina ; Cantor, Mircea ; Creed, Martin ; Delrue, Ronny ; Octavius Hill, David ; Adamson, Robert ; Elmgreen, Michael ; Dragset, Ingar ; Exner, Andreas ; Fogli, Andrea ; Grecu, Mihai ; Gross, Sabine ; Hubbard, Teresa ; Birchler, Alexander ; Jahnke, Katharina ; Klinger, Max ; Jooris, Tom ; Kwade, Alicja ; Maganias, DeAnna ; Martin, Kris ; Martin, Pia Maria ; Mosbacher, Alois ; Mundt, Wilhelm ; Muñoz, Oscar ; Nicolai, Olaf ; Klee, Paul ; Nuur, Navid ; Quantius, Olaf ; Ranner, Alexandra ; Sailstorfer, Michael ; Schwarzwald, Christian ; Schwontkowski, Norbert ; Sheng, Tianhong ; Richer, Gerhard ; Stahlschmidt, Jörn ; Starling, Simon ; Superflex ; Sugano, Maiko ; Tunn, Susanne ; Turk, Gavin ; Gober, Robert ; Van Severen, Hannes ; Vásquez de la Horra, Sandra ; Vordermaier, Sonja ; Wallinger, Mark ; Weizenfeld
Catalog of an exhibition: MARTa Herford Museum, Herford, September 4 - November 7, 2010.
Parallel texts in German and English.
kunstcatalogus